PELAKSANAAN CSR(CORPORATE SOCIAL RESPONSIBILITY) PADA PT. RIAU ANDALAN PULP AND PAPER DALAM PENYUKSESAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN DI KABUPATEN KAMPAR - Widya Novriza; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The background of this research is the phenomenon of CSR progam that has been optimal which is implemented by PT. Riau Andalan Pulp and Paper Integrated agricultural programs are optimal as contained in Law 40 of 2007 as well as grants provided such as providing field schools, monitoring farmer groups, providing annual funding, providing sustainable assistance of fertilizers and seeds. The purpose of this study was conducted to know and analyze Implementation of CSR (Corporate Social Responsibility) At PT. Riau Andalan Pulp and Paper In Successful Partnership Program and Community Development in Kampar District along with factors that influence it. The concept of theory used is to use Dimock's theory of planning, organizing, implementing. The type of research used is descriptive qualitative. Data collection was done by interview Officer CD PT. Riau Andalan Pulp and Paper, Head of Lipai River village, Community beneficiaries. Interview results were analyzed with qualitative analysis approach. The results showed that the implementation of CSR in an integrated agricultural program at PT. Riau Andalan Pulp and Paper is optimal. Because the implementation of the integrated program has reached the harvest that exceeds the target. It is influenced by several factors, namely: human, capital, documentation system, but there are still some factors that influence: natural factor that is weather and existence of society which less responsive in responding CSR program. Keywords: Planning, Organizing, Implementation